Ferrocene‐Containing Nucleic Acid‐Based Energy‐Storage Nanoagent for Continuously Photo‐Induced Oxidative Stress Amplification. (4th February 2022) - Ji, Cailing; Li, Hao; Zhang, Lei; Wang, Ping; Lv, Yawei; Sun, Zhijun; Tan, Jie; Yuan, Quan; Tan, Weihong
Abstract: Regulation of cellular oxidative stress plays a critical role in revealing the molecular mechanisms of cellular activities and thus is a potential strategy for tumor treatment. Optical methods have been employed for intelligent regulation of oxidative stress in tumor regions. However, long‐time continuous irradiation inevitably causes damage to normal tissues. Herein, a ferrocene‐containing nucleic acid‐based energy‐storage nanoagent was designed to achieve the continuous photo‐regulation of cellular oxidative stress in the dark. Specifically, the photoenergy stored in the agent could convert effectively and accelerate Fenton‐like reaction continuously, augmenting cellular oxidative stress. This nanoagent could also silence oxidative damage repair genes to further amplify oxidative stress. This strategy not only provides oxidative stress regulation for studying the molecular mechanisms of biological activities, but also offers a promising step toward tumor microenvironment modulation. Abstract : The siRNA‐aptamer‐ferrocene modified persistent luminescence nanoparticle (siRNA‐ApFe‐PLNP) was designed as an energy‐storage nanoagent to achieve continuous amplification of oxidative stress after photo‐activation, eliminating the need for constant light irradiation and further avoiding the photo‐induced tissue damage.